Survei Minat Pelajar Terhadap Ekstrakurikuler Wall Climbing di SMA Negeri 1 Babat Kabupaten Lamongan Tahun 2023 - Thoriqul Huda (Student Research Journal, 2024)
Extracurricular activities are activities organized by schools outside of class hours in the form of additional. Extracurricular activities are not mandatory for students but the benefits are no less important than the academic knowledge that students get at school during teaching and learning activities. Students motor skills can be trained or improved when doing extracurricular activities both in sports, arts, and other fields. This research was motivated by students who prefer to participate in futsal, basketball, and volleyball extracurricular activities compared to participating in Wall Climbing extracurricular activities at Senior High School 1 Babat and aims to determine the level of student interest in extracurricular Wall Climbing at Senior High School 1 Babat Lamongan in 2023. Later, the results of the research will be notified to the Wall Climbing extracurricular coach at SMA Negeri 1 Babat to be used as evaluation material for the extracurricular development of Wall Climbing Senior High School 1 Babat in a better direction. This research is a quantitative descriptive research with a research target of 15 students who are members of the Wall Climbing extracurricular at Senior High School 1 Babat in 2023. In this study, data was obtained from the results of questionnaire distribution and descriptive analysis techniques, namely by using the technique of calculating the average or mean. The results of this study are that all students who are members of the Wall Climbing extracurricular at Senior High School 1 Babat in 2023 are included in the high interest category with a percentage of 66,67%, with details of 10 students belonging to the high interest category, 2 students of very high interest level, and 3 students of low interest level. Calculate the statistics of this study reviewed through internal aspects consisting of indicators of attention, curiosity, motivation, needs and external aspects consisting of indicators of parental encouragement, encouragement of teachers, colleagues, facilities and infrastructure, environment. Student interest in extracurricular Wall Climbing at Senior High School 1 Babat is included in the high category interest with an average score of 135,2 from the highest score of 165, a percentage of 66,67% with details of 10 students. The internal aspect is included in the high category of interest with an average score of 57 out of the highest score of 68, a percentage of 60% with details of 9 students. The external aspect is included in the high category of interest with an average score of 78,2 from the highest score of 99, a percentage of 60% with details of 9 students. It can be concluded that students interest in extracurricular Wall Climbing at Senior High School 1 Babat in 2023 is included in the high category of interest.